Inundation risk assessment of metro system using AHP and TFN-AHP in Shenzhen. (May 2020) - Lyu, Hai-Min; Zhou, Wan-Huan; Shen, Shui-Long; Zhou, An-Nan
Highlights: Both AHP and TFN-AHP were incorporated into GIS to evaluate inundation risk. Inundation risk of metro system was evaluated based on regional risks along metro lines. Comparation between AHP and TFN-AHP assessment results were analyzed. The results were validated by "4.11 flood event" in Shenzhen, China. Abstract: Metro system is a vital transportation infrastructure, which has been inundated frequently during flood season (from May to September) in Shenzhen, China. This study incorporates the original analytic hierarchy process (AHP) and triangular fuzzy number-based AHP (TFN-AHP) into a geographic information system (GIS) to assess the inundation risk of the metro system in Shenzhen. The assessed results are verified by the 11 flood locations in the flood event that happened on April 11, 2019 (hereafter called the "4.11 flood event"). The risk indicators of the 11 flood locations derived from the TFN-AHP are greater than those obtained from the AHP. Most of the metro lines of the higher-risk and highest-risk match the regions with high inundation risks. The percentages of the higher-risk and highest-risk levels of the metro system obtained from TFN-AHP are greater than those from the AHP. The comparative result indicates that the TFN-AHP method can assess the inundation risk more distinctively than the original AHP.